Investigation of a Simple and Versatile Concept for OFDM Radar Target Simulator Enhancement - Birkenhauer, Christoph; Körner, Georg; Stief, Patrick; Hamberger, Gerhard; Beer, Matthias; Carlowitz, Christian; Vossiek, Martin (2024 IEEE Radio and Wireless Week, RWW 2024 - 2024 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2024, 2024)
This paper investigates the use of a modulation technique for radar target simulators (RTSs) that significantly improves their performance regarding dynamic range and multi angle capabilities. The technique, which has been examined for frequency-modulated continuous wave (FMCW) previously, is also applicable to orthogonal frequency-division multiplexing (OFDM) radar RTSs. It allows increases in the dynamic range and a finer gain adjustment by adjusting the mean value of the modulation. In addition, a low-cost multi-angle RTS can be realized using this approach by combining established RTS techniques with an additional suitably designed on-off modulation. While the advantages of this approach have already been demonstrated for FMCW radar sensors, this work focuses on the applicability of the technique to OFDM radars. A practical implementation of the proposed RTS enhancement technique is experimentally investigated for an experimental OFDM radar system. Our results show that the proposed method offers great practical advantages for improving RTSs even for multi-carrier radar signals, especially when cost is a major concern.
CRIS-Team Scopus Importer:2024-03-15
Keywords: automotive radar; OFDM radar; radar target simulation